2019
DOI: 10.1111/ecc.13202
|View full text |Cite
|
Sign up to set email alerts
|

The effect of web‐based education on Pap smear behaviours of teachers

Abstract: Objective Web‐based education would be useful for gaining health‐related behaviours. The aim of the study was to determine the effect of web‐based education on Pap smear behaviours of teachers. Methods The study was an experimental–control groups with a longitudinal type. The sample consisted of 1,290 teachers (experimental: 678, control: 612). The educational videos about cervical cancer and Pap smear test were sent to the experimental group via the web. Three months later, the teachers in both groups were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Hence, the training was found to be effective on the promotion of the women’s attitude and behavior regarding the performance of screening. Although the used educational method was not similar to that utilized in the current study, the results indicated the women’s need for a professional educational program, in order to improve their attitude and behavior regarding screening programs [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the training was found to be effective on the promotion of the women’s attitude and behavior regarding the performance of screening. Although the used educational method was not similar to that utilized in the current study, the results indicated the women’s need for a professional educational program, in order to improve their attitude and behavior regarding screening programs [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ampofo et al concluded that video-based educational intervention is an effective approach for improving cervical cancer awareness ( 35 ). Karakuş et al also reported that web-based intervention was observed to increase the Pap smear test behaviour among Indonesian teachers ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…The day-to-day utilisation of the internet in the health sector has upsurge in recent years, and individuals can readily obtain any information. Web-based education (WBE) with incredible visual and audio educational resources, gives individuals the opportunity to obtain information anywhere there is an internet accessibility, and allows individuals to revisit the website, to study and understand ( 25 ). Web-based education is indicated to be cost-effective, satisfactory, suitable and effective.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the journal, Karakuş Selçuk and Yanikkerem (2019) describe a web‐based intervention to improve participation in cervical cancer screening. Like many such interventions, they demonstrate a benefit in this mixed methods study.…”
mentioning
confidence: 99%